Thematic Analysis and Game-based Learning for the Development of Virtual Cultural Heritage Museums as Learning Agents - Ahmad Zainul Fanani; Arry Maulana Syarif; Deddy Award Widya Laksana; Heribertus Himawan; Hanny Haryanto (Techno.Com)
This study aims to develop a virtual cultural heritage museum as a learning agent. Qualitative approach with thematic analysis method was applied to design a virtual museum based on the perspective of museum management as a provider of learning facilities. The opinions collected were in the form of challenges and obstacles in functioning the museum as a provider of learning facilities. Opinions were used to identify the theme of the virtual museum, and synthesized with six strategies in effective learning. The resulting synthesis was then used to develop a virtual museum model using a game-based learning approach. The Photogrammetry technique was used for 3D reconstruction of cultural heritage objects to achieve high precision results, both in terms of shape and texture. The evaluation conducted using the User Accaptence Test technique shows that the proposed model and method can actualize the characteristics of effective learning strategies.